2013
DOI: 10.1177/1060028013510699
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Pathophysiology, Etiology, and Treatment of Attention-Deficit Hyperactivity Disorder (ADHD)

Abstract: Published research shows the benefit of drug therapy for ADHD in children, but given the poor adverse effect and drug interaction profiles, these must be dispensed with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
334
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 413 publications
(351 citation statements)
references
References 114 publications
(159 reference statements)
7
334
0
10
Order By: Relevance
“…An unexpected finding was the high rate of patients treated with methylphenidate or modafinil in the group of patients with steatosis hepatis. Methylphenidate is widely used in the treatment of children with attention deficit hyperactivity disorder (41) and is also used, as is modafinil, to treat secondary narcolepsy and severe daytime sleepiness in CP patients (42). Our original evaluation found 50% of our patients with steatosis hepatis were Rec.…”
Section: Discussionmentioning
confidence: 99%
“…An unexpected finding was the high rate of patients treated with methylphenidate or modafinil in the group of patients with steatosis hepatis. Methylphenidate is widely used in the treatment of children with attention deficit hyperactivity disorder (41) and is also used, as is modafinil, to treat secondary narcolepsy and severe daytime sleepiness in CP patients (42). Our original evaluation found 50% of our patients with steatosis hepatis were Rec.…”
Section: Discussionmentioning
confidence: 99%
“…Atomoxetine is considered to be particularly beneficial as an adjunct therapy in ADHD patients presenting tics and comorbid anxiety (14)(15)(16). As it is devoid of abuse potential, atomoxetine is regarded as an appropriate alternative to the drugs that are misused (17).…”
Section: Discussionmentioning
confidence: 99%
“…Despite being one of the most extensively studied psychiatric disorders, the pathophysiology underlying ADHD symptoms remains only poorly understood (Albrecht et al 2015;Sharma and Couture 2014;Thapar et al 2013). A vast amount of research demonstrated that ADHD has strong biological underpinnings, including abnormalities in neurotransmitter systems in the brain.…”
Section: Introductionmentioning
confidence: 99%